Two-stage surgical management of horseshoe lung associated with congenital pulmonary airway malformation in a neonate: A case report - Veronica Polit-Guerrero; Jimmy Andrade-Montesdeoca; Ernesto Fabre-Parrales; Vicente Salinas-Salinas; Daniel Acosta-Farina (EL-Med-Pub, 2023)
Background: Horseshoe lung is a rare congenital malformation, and even rarer is its association with congenital pulmonary airway malformations. Case Presentation: We report a case of horseshoe lung associated with congenital pulmonary airway malformation (Stocker type 2) who underwent surgical management in two stages. The patient had a right posterolateral thoracotomy with lower right lobectomy at 14 days of life, followed by a left posterolateral thoracotomy with lower left lobectomy at 7 months of age. He is doing fine after both surgeries and follow-up visits are ongoing. Conclusion: The treatment of horseshoe lung should be individualized, surgical management is an effective option and the two-stage approach in neonates would reduce the risk of the simultaneous bilateral procedure.